2006
DOI: 10.1055/s-2006-954862
|View full text |Cite
|
Sign up to set email alerts
|

Recall of Hearing Aid Orientation Content by First-Time Hearing Aid Users

Abstract: Recall of hearing aid orientation (HAO) information by new hearing aid users was assessed in this pilot study. Twenty-eight older adults completed a 25-item recall test of hearing aid knowledge that contained questions targeting information presented during a typical HAO. The mean recall score immediately following the HAO was 80%. The mean recall score at the hearing aid follow-up 4 weeks later was 77%, indicating that most of the information was retained. Recall scores were not significantly different based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…These pieces of information corroborate with the results obtained and discussed before, regarding the users´ performance in the use, manipulation and cleaning of the HA/earmold. Another fact that confirms the results found by the studies mentioned (7,10,12,26) is what two participants reported about not knowing the meaning of the "beep" until watching the DVD and what other two participants reported, pointing the "cotton bud" as the correct way of dealing with the excess of wax in the external auditory canal, also mentioning, that the DVD had such information and emphasized the importance of looking for a otorhinolaryngologist to solve this problem.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These pieces of information corroborate with the results obtained and discussed before, regarding the users´ performance in the use, manipulation and cleaning of the HA/earmold. Another fact that confirms the results found by the studies mentioned (7,10,12,26) is what two participants reported about not knowing the meaning of the "beep" until watching the DVD and what other two participants reported, pointing the "cotton bud" as the correct way of dealing with the excess of wax in the external auditory canal, also mentioning, that the DVD had such information and emphasized the importance of looking for a otorhinolaryngologist to solve this problem.…”
Section: Discussionsupporting
confidence: 77%
“…Although, literature mentions that besides the level of information retained by the individuals, in the guidance process, be low compared with the level of information provided (10,12,26) , a lot of information is remembered incorrectly (7) . These pieces of information corroborate with the results obtained and discussed before, regarding the users´ performance in the use, manipulation and cleaning of the HA/earmold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation could be that, because the AVE listening demonstrations took place during the visit at which participants wore their hearing aids for the first time, and received the hearing aid orientation regarding use, upkeep, and maintenance of the hearing aids, the message from the demonstrations was forgotten by the time they left the laboratory, or missed altogether. As reported by Reese and Smith (2006) and Reese and Hnath-Chisolm (2005), new hearing aid users only recall between 70 and 75% of the information provided at hearing aid orientation. This means that as much as 25% of the information is either lost or misunderstood.…”
Section: Effect Of Counseling On Expectationsmentioning
confidence: 78%
“…It has been suggested that between 56 40-80% of information given verbally in clinical appointments is forgotten afterwards 57 (Kessels, 2003). A study of hearing aid users showed that of the information delivered at the 58 hearing aid fitting appointment, a more optimistic figure of 25% is forgotten one month later 59 (Reese & Smith, 2006). However, this study used a multiple-choice method of assessment 60 that may have artificially inflated the amount of information recalled.…”
mentioning
confidence: 91%